SWOT Analysis of Galuga Final Disposal Site - Azka fadilla setiawan; Alimuddin Alimuddin; Rulhendri Rulhendri; Fadhila Muhammad Libasut Taqwa (Journal of Applied Geospatial Information, 2022)
In activities, the community produces waste so that the production of waste is increasing over time. For this reason, it is necessary to carry out effective and efficient waste management. This study aims to determine the strategy of waste management managed by the Environmental Agency at the Galuga Landfill, Galuga Village, Cibungbulang District, Bogor Regency, in this study used descriptive research methods using a qualitative approach. The informants in this study were the Waste Management Section, the Head of the Galuga Landfill, Garbage Transport Officers, Community Leaders, and local residents. The collection of data and information is done by means of interviews, and documentation. The data analysis technique used is SWOT analysis by taking into account all internal and external aspects of the organization, namely strengths, weaknesses, opportunities, and threats. Based on the results of the SWOT calculation, the Galuga solid waste subsector is in quadrant one, namely internal and external strong, with the result that the value of the difference between strengths and weaknesses on internal factors shows a positive value and the value of the difference between opportunities and threats on external factors also shows positive, so the strategy what will be developed to overcome strategic issues that arise is an aggressive strategy in implementing landfill management, such as establishing a waste zoning pattern, improving services and efforts to reduce waste through 3R.